Subcutaneous Cavernous Cervicofacial Lymphangioma and It's Surgical Treatment in a Calf - Eroksuz, Yesari; Unsaldi, Emine; Tanrisever, Murat; Incili, Canan Akdeniz; Eroksuz, Hatice (Kafkas Univ, Veteriner Fakultesi Dergisi, 2021)
A 20-day-old, Simmental male calf showed a subcutan mass locating left side of chin, buccal and neck regions. The mass covering the 70% of left side of the face consisted of cystic structures under the skin. It was surgically excised and no recurrence occurred three months after the excision. The cut surfaces of mass were measured by 20x15x8 cm in size. Histologically, the mass was diagnosed as cavernous lymphangioma which composed of thin-walled cystically dilated spaces which were lined with one or rarely more layers of flat endothelial cells. Mitotic figures were not present. The channels did not contain red blood cells in contrast to, endothelial cells lining adjacent blood vessels. The endothelial cells of cystic dilated spaces gave positive cytoplasmic immunoreaction forpodoplanin. In conclusion, this report presents clinical, pathological, immunohistochemical features and surgical treatment of cervicofacial lymphangioma in a calf.
Keywords: Bovine; Calf; Lymphangioma; Pathology; Immunohistochemistry; Surgical treatment